Gaya Bahasa dalam Kritik Sosial pada Lagu-Lagu Karya Iwan Fals - Nurhayati Fokaaya (Kantor Bahasa Provinsi Maluku Utara, 2015)
Iwan Fals’ song lyrics are likely to present social realities. This is a way to express the criticism of injustice to the government. The research uses semantic theory to analyze Iwan Fals’ lyrics of songs. The aim is to describe the meaning of social criticisms from those lyrics. The method is a qualitative method by using descriptive approach. The results of this study show social criticisms in the lyrics by Iwan Fals in the years of 1981–1995 describe the issues of corruption, law enforcement, poverty, unemployment, and collusion. to express them, the author uses the style of figurative language such as metaphor and personification. One of his criticisms can be seen in the lyrics, Tikus-tikur Kantor (1984), Galang Rambu Anarki (1981), Sarjana Muda (1981), Orang Pinggiran (1995), and Surat Buat Wakil Rakyat (1987).